Mekanisk drivning vid slakt och dess effekt på nötkreaturens (Bos taurus) beteende - Lodnert, Denice (2018)
The Swedish human population´s beef consumption is high and in recent years, more consumers have gained insight regarding obtained values when buying meat produced in Sweden. With an increased awareness, the demands on meat production also increases. Slaughter is a part of the meat production where the risk of impaired animal welfare is present. At the slaughterhouse, animals are exposed to several stressful stimuli, for example when being driven to the stun box. Cattle (Bos taurus) are often divided into dairy and beef breeds. Separate selection strategies have been applied for the different breeds which entails a variation regarding temperament. This may cause different reactions to handling by stock personnel. The reactions also depend on animal sex and age. Previous research has proven observations of cattle behaviour to be a suitable method for evaluating the stress level. A study was conducted at a Swedish slaughter plant where an observational study of cattle behaviour during driving to the stun box was executed. After the study a mechanical gate was installed for automatic driving of the animals. This study was carried out in order to examine whether the mechanical gate had an effect on manual driving practices, animal behaviours related to stress and the time for driving. Differences between animal breeds or sexes were also examined. The cattle displayed less stressful behaviour after installation of the mechanical gate. The time spent in the driveway to the stun box was not affected but the time spent in the stun box decreased. Cattle of beef breed spent longer time in the stun box compared to cattle of dairy breed. This may imply that the former were more stressed by being confined in the stun box. Heifers exhibited more of the behaviour categorized as ‘clear stressful behaviour’ than other animal categories, while steers exhibited less. These results confirm previous research findings and indicate that mechanical driving of cattle can be a way to decrease animal stress from manual handling at driving to the stun box. The results should be seen as an incentive for further research on mechanical driving, its impact on animal welfare and work conditions for employees at the slaughterhouse.